Peaks
Se compilan cuatro obras del estudio francés Peaks. Contiene: Pavillon de L'Amour. Lac des Sapins. Aix. Augures.
Keywords: FRANCIA; AIX-EN-PROVENCE; VERSALLES; PABELLONES; CENTROS RECREATIVOS; RENOVACIÓN; RENOVACION ARQUITECTONICA; PROYECTOS; MAQUETAS; CIUDADES; ECOLOGIA; AUBERTIN, CHARLES; DUPONT, CAMILLE; MALOISEL, ÉVA; NANÇAY; CUBLIZE